The Extent of New Product Development Partnership between Universities and the Manufacturing Firms in Ghana - Munkaila, Alhassan; Clinton, Aigbavboa; Wellington, Didibhuku. Thwala (International Journal of Engineering and Management Research, 2021)
The importance of new product development in building both technological and technical capacity of university and firm cannot be overemphasized. Collaborations between HE and industry in NPD is conceived as mutual interaction for skills acquisition and economic improvement. The study was designed to determine the extent of new product development partnership between HEIs and the manufacturing firms. A survey was conducted, and a sample of 400 was drawn from both HE and industry; the data were then analyzed using structural equation modeling (SEM) software of EQS version 6.2.The results revealed that there is weak interaction between HE and industry, also there is no formal partnership between the two on new product development. in order to strengthen the mutual relationship, a conceptual model had been developed after a careful examination and assessment of the key factors of NPD and after preliminary CFA analysis conducted to establish the determinants of the main construct. A nine-factor model was then developed for university and industry. The study therefore recommends that higher education and industry adopt this new model for effective partnership on NPD.